Penerapan Konsep Arsitektur Tropis pada Bangunan Gereja Katolik Santo Asisi, Padang Bulan, Medan - Sagala, Peranita; Saragih, Rehulina (Universitas Medan Area, 2024)
Indonesia is one of the countries with tropical climate. Hot conditions, humid air and high rainfall require architectural solutions that are responsive to the climate. It is common in Indonesia to use the concept of tropical architecture. Santo Fransiskus Asisi Catholic Church, Padang Bulan is one of the buildings that applies tropical architecture. This building is located in Medan Selayang sub-district and uses several applications of tropical architecture as a solution to problems in tropical climates. This research aims to see the extent to which tropical architecture is applied in this church building. The method used is descriptive explanatory, which describes the parts of the space and building with its response to the tropical climate. The results show some applications of tropical architecture in this building, such as the use of ventilation, sloping roofs, terraces and the use of local materials.